SOME PROBLEMS RELATED TO THE STUDY OF FIGURATIVE VERBS IN THE KYRGYZ LANGUAGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses some issues related to the study of figurative verbs in the kyrgyz language. In kyrgyz linguistics, figurative verbs were considered mainly in morphological aspect, and their lexico-semantic, stylistic, functional, etc. The specifics have not yet been the subject of study. In this regard, the article identifies some issues related to these aspects of figurative verbs.
Keywords: kyrgyz language, verbs, figurative verbs, morphological aspect, root, lexico-semantic, stylistic, specificity, sound form